Financial Knowledge, Saving and Investment Behaviour among Women: A Review - Singh, Khujan; Berwal, Kavita (The journal of contemporary issues in business and government, 2021)
Financial knowledge is all about having financial awareness and understanding of various financial concepts and procedures. It also includes the proper application of this understanding in solving financial problems. Many countries are carrying out financial literacy surveys (particularly on their women section), thereby providing an insight into saving and investment-related knowledge as well as financial behavior. This paper is intended to review the literature relating to the level of financial knowledge among women section as well as to know the type of relationship financial knowledge holds with saving and investment behavior. The study also looked into the factors affecting both financial knowledge and saving & investment behavior of individuals. Along with this, do financial education courses or programs impact saving and investment behavior or not.